Virtual mirrors: Social media’s role in body dissatisfaction and disordered eating habits in Cyprus - Davradou, Claire; Argyridis, Marios (Psychology: the Journal of the Hellenic Psychological Society, 2025)
Social media platforms (e.g., Instagram, Facebook, TikTok) have become an integral part of daily life, shaping perceptions, behaviours, and social norms with positive and negative effects. This study aimed to examine the correlation of passive and active social media use on body satisfaction and disordered eating habits. Passive use refers to content consumption without interaction (e.g., viewing celebrities’ posts), while active use involves direct and/or indirect user interaction (e.g., posting, manipulation photos). Gender differences in passive and active social media use and body image were also explored. The study involved 3,504 Cypriot participants (mean age = 36.87, 66.8% female) who responded to multiple measures on social media use, body satisfaction and disordered eating and employed stepwise linear regression and independent samples t-tests for data analysis. The results revealed that, for men, the factors associated with body dissatisfaction included the consumption of fitness posts, posting, manipulation, and investing in photos. Conversely, for women, associated factors were viewing celebrities/fashion/beauty posts, friends’, and peers’ posts, posting, manipulation, investing in photos, as well as the importance of likes and comments. Regarding disordered eating, men’s associated factors were viewing celebrities/fashion/grooming posts, manipulation, investing in photos, and the importance of likes and comments. In contrast, women’s associated factors included viewing fitness posts, manipulation, investing in photos, and the importance of likes and comments. Gender differences were observed in all variables, except for taking and posting photos. These findings underscore the complex relationships between passive and active social media use and body image in Cyprus. The results emphasize the need for targeted interventions and prevention strategies to promote positive body image and mitigate the risk of disordered eating habits, considering the gender-specific correlations integral to engagement.